2013
DOI: 10.1007/s10753-013-9742-8
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 6(-174G/C) Variant and its Circulating Levels in Coronary Artery Disease Patients and Their First Degree Relatives

Abstract: Interleukin-6 (IL-6) a pleiotropic cytokine is a central mediator of inflammation in the pathogenesis of coronary artery disease (CAD). Our aim is to evaluate the serum levels of IL-6 and C-reactive protein (CRP) and to analyze the IL-6 polymorphism in CAD patients and to identify the first-degree relatives (FDRs) at risk of the disease in comparison with healthy controls. Estimation of IL-6 levels by enzyme-linked immunosorbent assay (ELISA) and CRP by latex reagent kit method, and genotyping of IL6 gene vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 31 publications
0
13
0
1
Order By: Relevance
“…Recently, some metaanalyses suggested that IL-6 polymorphism (e.g., -174G/ C and -572G/C) is associated somewhat with CAD risk [54]. Although relevant meta-analysis gained summary results, several new studies reported conflicting results [36][37][38]. In the present study, the association was analyzed in Caucasian (including European and South Asian) and East Asian populations comprehensively, and the different associations were explained based on ethnicity.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Recently, some metaanalyses suggested that IL-6 polymorphism (e.g., -174G/ C and -572G/C) is associated somewhat with CAD risk [54]. Although relevant meta-analysis gained summary results, several new studies reported conflicting results [36][37][38]. In the present study, the association was analyzed in Caucasian (including European and South Asian) and East Asian populations comprehensively, and the different associations were explained based on ethnicity.…”
Section: Discussionmentioning
confidence: 88%
“…It has been reported that IL-6 gene polymorphisms contribute significantly to CAD , but the results of previous studies were inconsistent. Although relevant meta-analysis gained summary results, several new studies reported conflicting results [36][37][38]. We designed the meta-analysis involving all previous eligible studies to assess the association of IL-6 polymorphisms with CAD.…”
Section: Introductionmentioning
confidence: 99%
“…Many epidemiologic studies have observed that polymorphisms in the genes encoding interleukin-1 receptor antagonist, such as , are associated with the development of CAD (Zhang et al, 2011;Huang et al, 2013;Opstad et al, 2011Opstad et al, , 2013Galimudi et al, 2014;He et al, 2014;Zhang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…One animal experimental study has shown that several cytokines play a key role in the development of CAD (Kleemann et al, 2008). Several previous epidemiology studies have shown that polymorphisms in several cytokines, including interleukin-6 (IL-6), , are involved in the pathogenesis of CAD (Zhang et al, 2011;Huang et al, 2013;Opstad et al, 2011Opstad et al, , 2013Galimudi et al, 2014;He et al, 2014;Zhang et al, 2014). However, the results of these studies are inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…genotypes [38]. There have been no studies of the effects of IL-6 promoter polymorphisms on IL-6 levels after stroke.…”
Section: Accepted Manuscriptmentioning
confidence: 99%